Information network and data communication teleservice architecture and engineering : proceedings of the IFIP/ICCC International Conference on Information Network and Data Communication, Trondheim, Norway, June 1996 - Khakhar, Dipak; Aagesen, Finn Arve; Botnevik, Harald (Chapman & Hall, 1996)
Teleservices represent a diversity of applications related to various user and vendor cultures such as traditional telecommunication services, e-mail services, co-operative work applications, multimedia applications, mobile services and intelligent network services. The complexity and diversity of teleservices is constantly increasing. In addition, the way teleservices are designed, delivered and maintained is changing. The objective of this text is to capture the cultural and technical variety of teleservices. The following topics are covered: architectures for traditional and new teleservices; platform functionality and software; telecommunication infrastructure and fault-tolerant databases for real-time teleservice execution; and methodology, FDTs and languages. It contains the selected proceedings of the Sixth Conference on Information Network and Data Communication, held in Trondheim, Norway, 1996, and sponsored by the International Federation for Information Processing. This book should be valuable reading for telecom software and hardware manufacturers, and educational researchers working in related areas.